Training Spatial Skills in Men and Women. Issue 1 (August 2014) - Cherney, Isabelle D.; Bersted, Kyle; Smetter, Joseph
Recent studies suggest that even short-term video game training may transfer to other cognitive tasks. With the popularity of the Nintendo Wii with women, more of them might be exposed to the games that will increase their mental rotation skills. Because performance on mental rotation tests (MRT) has been linked to math performance in women, and thus may ultimately contribute to the under-representation of women in STEM fields, it is important to continue to explore ways to decrease or eliminate the robust sex difference in mental rotation. The present study of 30 men and 30 women provides additional evidence that women may benefit from short-term (1 hour) training on either a Nintendo Wii™ or GameCube console to increase their mental rotation skills. One hour of video game training not only increased women's MRT scores to a level similar to men's scores, but also produced greater average improvement for women, even when controlling for experiential factors such as spatial and masculine childhood activities that could contribute to the sex difference in spatial ability.